Influence of water vapour on selected ion flow tube mass spectrometric analyses of trace gases in humid air and breath - Spanĕl, P; Smith, D (Rapid communications in mass spectrometry, 2000)
Selected ion flow tube mass spectrometry (SIFT-MS) detects and quantifies in real time the trace gases, M, in air/breath samples introduced directly into a flow tube. Inevitably, relatively large partial pressures of water vapour are introduced with the sample and the water molecules become involved in the ion chemistry on which this analytical technique depends. When H(3)O(+) ions are used as the precursors for chemical ionisation and SIFT mass spectrometric analyses of M, they generally result in the formation of MH(+) ions. Also, when water vapour is present the H(3)O(+) ions are partially converted to hydrated hydronium ions, H(3)O(+).(H(2)O)(1,2,3). The latter may act as precursor ions and produce new product ions like MH(+).(H(2)O)(1,2,3) via ligand switching and association reactions. This ion chemistry and the product ions that result from it must be accounted for in accurate analyses by SIFT-MS. In this paper we describe the results of a detailed SIFT study of the reactions involved in the quantification of acetone, ethyl acetate, diethyl ether, methanol, ethanol, ammonia and methyl cyanide by SIFT-MS in the presence of water vapour. This study was undertaken to provide the essential data that allows more accurate analyses of moist air and breath by SIFT-MS to be achieved. It is shown using our standard analysis procedure that the error of SIFT-MS quantification caused by the presence of water vapour is typically 15%. An improved analysis procedure is then presented that is shown to reduce this error to typically 2%. Additionally, some fundamental data have been obtained on the association reactions of protonated organic molecules, MH(+) ions, with water molecules forming MH(+).H(2)O monohydrate ions. For some types of M, reaction sequences occur that lead to the formation of dihydrate and trihydrate ions.
Keywords: Air; algoritmy; reprodukovatelnost výsledků; vlhkost; Breath Tests; Kinetics; Water; Solvents; vzduch; Algorithms; hmotnostní spektrometrie; Reproducibility of Results; dechové testy; kinetika; voda; rozpouštědla; Mass Spectrometry; Humidity